48.7k views
4 votes
Choose a method (factoring. square root property, completing the square, and the quadratic formula) to solve each of the following quadratic equations.

Each method can be used only ONCE

A) 4x2 – 27 = 0

B) 4x2 – 8x – 5 = 0

C) 4x2 – 8x – 12 = 0

D) 4x2 – 9x – 7 = 0

User Bertilio
by
5.0k points

1 Answer

4 votes

Answer:

Part A)
x=(+/-)(3√(3))/(2)

Part B)
x=2.5 and
x=-0.5

Part C)
x=-1 and
x=3

Part D)
x=(9+√(193))/(8) and
x=(9-√(193))/(8)

Explanation:

Part A) we have


4x^(2)-27=0

we know that

The square root property states that if we have an equation with a perfect square on one side and a number on the other side, then we can take the square root of both sides and add a plus or minus sign to the side with the number and solve the equation.

isolate the term that contains the squared variable


4x^(2)=27


x^(2) =(27)/(4)

take the square root of both sides


x=(+/-)(√(27))/(2)

simplify


x=(+/-)(3√(3))/(2)

Part B) we have


4x^(2)-8x-5=0

Using the quadratic equation

The formula to solve a quadratic equation of the form


ax^(2) +bx+c=0 is


x=\frac{-b(+/-)\sqrt{b^(2)-4ac}} {2a}

in this problem we have


4x^(2)-8x-5=0

so


a=4\\b=-8\\c=-5

substitute in the formula


x=\frac{-(-8)(+/-)\sqrt{-8^(2)-4(4)(-5)}} {2(4)}


x=(8(+/-)√(144))/(8)


x=(8(+/-)12)/(8)


x=(8(+)12)/(8)=2.5


x=(8(-)12)/(8)=-0.5

Part C) we have


4x^(2)-8x-12=0

Using Factoring

Simplify the expression first

Divide by 4 both sides


x^(2)-2x-3=0

Find two numbers a and b such that

a+b=-2

ab=-3

Solve the system by graphing

The solution is a=1, b=-3

see the attached figure

so


4x^(2)-8x-12=4(x-1)(x+3)

The solutions are


x=1, x=-3

Part D) we have


4x^(2)-9x-7=0

Solve by completing the square

Group terms that contain the same variable, and move the constant to the opposite side of the equation


4x^(2)-9x=7

Factor the leading coefficient


4(x^(2)-(9)/(4)x)=7

Complete the square. Remember to balance the equation by adding the same constants to each side


4(x^(2)-(9)/(4)x+(81)/(64))=7+(81)/(16)


4(x^(2)-(9)/(4)x+(81)/(64))=(193)/(16)

Rewrite as perfect squares


4(x-(9)/(8))^(2)=(193)/(16)


(x-(9)/(8))^(2)=(193)/(64)

take square root both sides


(x-(9)/(8))=(+/-)(√(193))/(8)


x=(9+√(193))/(8)


x=(9-√(193))/(8)

Choose a method (factoring. square root property, completing the square, and the quadratic-example-1
User Elp
by
4.5k points